A Critical Review of Teaching With Virtual Lab: A Panacea to Challenges of Conducting Practical Experiments in Science Subjects Beyond the COVID-19 Pandemic in Rural Schools in South Africa. (March 2022) - Shambare, Brian; Simuja, Clement
This paper is based on a systematic literature review of published research on the educational application of Virtual Lab. The paper focuses on the use of the mobile Virtual Lab application for learning science practicals in rural school context. This paper analyses the theoretical aspects of using VL in teaching and learning of science practical experiments. The previous studies published in national and international journals and conference proceedings on science education and technologies in education, and regarding the benefits of using VL in science education, are discussed as references for integrating VL in teaching of science practicals in the rural school context. A systematic review method was adopted in this paper to explore articles that focus on Virtual Labs and the use of Virtual labs in teaching and learning. However, the aim of this paper is to provide science teachers in rural schools and education policy makers with a better understanding of the constraints and the benefits of using VL technology in mediating learning of science practical experiments and encourage teachers to adopt the use of VL as technology for conducting science practical experiments. In addition, this paper also addresses the possible factors that may affect learners' learning of science practical experiments using VL technology in rural school educational settings, giving educational policy makers and curriculum developers enlightenment as to the effective integration of VL technology in science education. We conclude by providing suggestions and recommendations on the use of VL in teaching and learning of science practical experiments in rural schools beyond COVID-19 pandemic.